Highly porous nitrogen-doped carbon nanoparticles synthesized via simple thermal treatment and their electrocatalytic activity for oxygen reduction reaction. (May 2017) - Tachibana, Naoki; Ikeda, Saori; Yukawa, Yasuyuki; Kawaguchi, Masahiro
Abstract: This paper presents a materials study with the aim of obtaining nitrogen-doped porous carbon nanoparticles (NPCNs) with a fine pore network that provides efficient access for mass transport as well as abundant electrocatalytic active sites for oxygen reduction reactions (ORR). Carbon black (CB) after pretreatment by either heat or nitric acid was used as a carbon source. NPCNs were prepared using the pretreated CB impregnated with cyanamide via a simple thermal treatment. The pretreatment and the synthesis temperature have significant effects on the amount of nitrogen species present and pore structures of the NPCNs. Thermal treatment incorporates nitrogen into the carbon network but also increases the volume of pores larger than 2 nm in diameter and surface area. Heating of nitric acid-pretreated CB impregnated with cyanamide at 1000 °C gives NPCNs contained an optimal combination between the concentration of quaternary N and surface area. The NPCNs exhibited high activity for ORR in a rotating disk electrode system and were also effectively applied to a gas diffusion electrode. The specific current density normalized to the surface area depends on the quaternary N concentration, suggesting that quaternary N creates the active sites for ORR. Graphical abstract: